The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.socscimed.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Using conversation analytic methods to assess fidelity to a talk-based healthcare intervention for frequently attending patients

Abstract: The study aim was to assess implementation fidelity (i.e., adherence) to a talk-based primary care intervention using Conversation Analytic (CA) methods. The context was a UK feasibility trial where General Practitioners (GPs) were trained to use "BATHE" (Background,Affect,Trouble,Handling,Empathy) - a technique to screen for psychosocial issues during consultations - with frequently attending patients. 35 GPs received BATHE training between July-October 2015. 15 GPs across six practices self-selected to recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Further work is needed to explore the triage structure specifically for third-party callers. With increasing evidence that healthcare staff can be successfully trained in more effective talk practices using the lens of CA, 55 there may be ways that call-takers can be trained to design probing questions that are most congruent with third party callers’ own epistemic domain, and therefore avoid some of the interactional troubles that can delay triage progression.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to explore the triage structure specifically for third-party callers. With increasing evidence that healthcare staff can be successfully trained in more effective talk practices using the lens of CA, 55 there may be ways that call-takers can be trained to design probing questions that are most congruent with third party callers’ own epistemic domain, and therefore avoid some of the interactional troubles that can delay triage progression.…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented in this paper, in combination with other evidence collected during the wider feasibility study [4], [15], suggests BATHE is acceptable and potentially beneficial when used in Tables Table 1. The five elements of the BATHE technique and their related questions [5] 18.0 (0 -60.0)…”
Section: Resultsmentioning
confidence: 53%
“…Insights into these difficulties are valuable, and when combined with other findings from the pilot RCT and process evaluation [4] [15], help us to understand our quantitative findings regarding overall use of BATHE. Whilst feedback from study GPs suggested there was some under-reporting of its use, the extent of BATHE use was still lower than we might have hoped.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of recorded BATHE consultations ( n = 21) revealed adaptations in question composition and deviations from the training protocol. 25 Tailoring of questions to individual patient circumstances were considered successful adaptations. However, adaptations changing the nature of the questions and deviations in question location were consequential for theoretical fidelity to BATHE, and thereby its potential effectiveness.…”
Section: Resultsmentioning
confidence: 99%